Impact of COVID-19 on mental health of healthcare professionals working in COVID-19 designated clinical areas in India - Sharma, Kamlesh Kumari; Kaur, Ravneet; Srinivasan, Muthuvenkatachalam; Sarkar, Siddarth; Mani, Kalaivani; Sharma, Yamya; Gupta, Sandhya (International Journal Of Community Medicine And Public Health, 2021)
Background: In the wake of the pandemic of coronavirus disease 2019, there are reports of its impact on psychological wellbeing of the health care workers. Methods: This cross-sectional survey was conducted in June 2020 in a tertiary care hospital in Delhi, India among conveniently sampled 93 participants i.e. doctors and nurses directly engaged in clinical activities in COVID-19 designated areas. A self-administered questionnaire through Google forms elicited symptoms of depression, anxiety, insomnia, and distress measured using the 9-item patient health questionnaire, 7-item generalized anxiety disorder scale, 7-item insomnia severity index, and 22-item impact of event scale-revised respectively. Results: Majority (53.8%) of the participants were male and their mean age was 30.2 years. Most (72%) were nurses, the rest being doctors. A substantial proportion of the participants had depression (47.4% of the sample), anxiety (29.0%), insomnia (32.3%) and distress (22.6%). Symptoms were disproportionately higher in female and single participants, nurses; those with history of chronic illness, staying in institute provided temporary accommodation, working on regular basis and perceiving lack of adequate personal protective equipment. Taking prophylactic hydroxychloroquine was associated with lower symptom rates. Conclusions: This survey revealed a considerable prevalence of mental health outcomes in HCWs demonstrating an association with age, gender; marital, professional and employment status, history of chronic illness, access to PPE, stay at institute provided temporary accommodation and prophylactic hydroxychloroquine use.